2022
DOI: 10.3390/jof8111160
|View full text |Cite
|
Sign up to set email alerts
|

Trichocladium solani sp. nov.—A New Pathogen on Potato Tubers Causing Yellow Rot

Abstract: A new species, Trichocladium solani, was isolated from potato (Solanum tuberosum L.) tubers from Russia. The species has no observed teleomorph and is characterized morphologically by non-specific Acremonium-like conidia on single phialides and chains of swollen chlamydospores. Phylogenetic analysis placed the new species in a monophyletic clade inside the Trichocladium lineage with a high level of support from a multi-locus analysis of three gene regions: ITS, tub2, and rpb2. ITS is found to be insufficient f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The Trichocladium members were not reported as a pathogenic worldwide. However, a recent study in 2022 [19] was identified a new species, Trichocladium solani, that causes yellow rot on potato tubers. Therefore, further investigation should be conducted to confirm the pathogenicity of the T. asperum on the same ornamental plants and other plant hosts using efficient previous protocols applied on ornamental plants [20].…”
Section: Discussionmentioning
confidence: 99%
“…The Trichocladium members were not reported as a pathogenic worldwide. However, a recent study in 2022 [19] was identified a new species, Trichocladium solani, that causes yellow rot on potato tubers. Therefore, further investigation should be conducted to confirm the pathogenicity of the T. asperum on the same ornamental plants and other plant hosts using efficient previous protocols applied on ornamental plants [20].…”
Section: Discussionmentioning
confidence: 99%
“…The SpyderCheckr 48 comprises 48 color patches with known spectral reflectance values, facilitating the calibration and profiling of digital imaging devices to ensure accurate and consistent color reproduction. This tool is commonly employed in various fields, including photography, graphic design, and scientific imaging, to maintain fidelity in color representation across different devices and environments (Belosokhov et al, 2022;Ebner et al, 2021;Moore et al, 2021). Color calibration is done by applying the color calibration matrix obtained from Spydercheckr color parameters.…”
Section: Digital Image Acquisition Processing and Analysismentioning
confidence: 99%